Climate change scenarios, their impacts and implications on Indian cardamom-coffee hot spots; one of the two in the world - Muthusamy Murugan; M. Alagupalamuthirsolai; Kaliyaperumal Ashokkumar; Aavudai Anandhi; Raju Ravi; J. Rajangam; M. K. Dhanya; K. S. Krishnamurthy (Frontiers in Sustainable Food Systems, 2022)
In this study, we investigated climatic parameters and predicted future changes in precipitation and atmospheric temperature levels based on RCP4. 5/8.5 scenarios in all cardamom-coffee hot spots of southern India. Our results showed more precipitation levels and patterns occurred in Cardamom hills (Kerala), followed by lower Puleny hills in Tamil Nadu. The least variation in precipitation levels has been noticed for temperate upper Puleny hills and Kodagu hills in Karnataka. RCP4.5/8.5 scenario analysis showed greater variability in precipitation, up to 180% increase and 90% decrease for all hot sports. The scenario analysis also predicted extreme temperature variations ranging from 0.5 to 8.5°C increase for the entire study region. A significant change in coffee yield and quality has been recorded over the last 30 years. Increased yield trends in coffee were noticed for Cardamom hills (CH) and Kodagu hills, but significantly lower coffee production was observed for lower Pulney hills. The mixed response of yield variability in coffee has been primarily attributed to the ongoing changing climatic factors. Ecophysiological studies of coffee, cardamom, and black pepper have proved that coffee would adapt well to future challenging climatic conditions, closely followed by cardamom and black pepper. Since all the coffee-cardamom hot spots in southern India undergoes considerable change in precipitation levels and pattern, necessary precautions, including water and irrigation management strategies, must be given utmost priority to increase the crop yield sustainability of these delicate cardamom-coffee hot spots in India.